Using Questions Box in Teaching Simple Past Tense - Shanty Halim (Universitas Cokroaminoto Palopo, 2016)
This research is aimed at finding out to find out whether the use of questions box effective in teaching simple past or not. This research used pre-experimental method. Furthermore, this research was conducted at Politeknik Negeri Ujung Pandang. There were 20 students as sample. The findings of this research show that using questions box is effective in teaching simple past tense. It was proven by the significant difference between the students’ mean score in pretest and posttest when used SPSS program. There was significant different ability of the students before giving treatment and after giving treatment. In the pretest, the mean score of the students pretest was 2.32 and the mean score of posttest was 7.52. Standard deviation of pretest was 1.42 and the standard deviation of posttest was 0.75. The researcher also found that the students have positive interest toward the use of questions box in teaching simple past tense at Politeknik Negeri Ujung Pandang.